IGARSS 2022 - 2022 IEEE International Geoscience and Remote Sensing Symposium 2022
DOI: 10.1109/igarss46834.2022.9883897
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty-Guided Representation Learning in Local Climate Zone Classification

Abstract: A significant leap forward in the performance of remote sensing models can be attributed to recent advances in machine and deep learning. Large data sets particularly benefit from deep learning models, which often comprise millions of parameters. On which part of the data a machine learner focuses on during learning, however, remains an open research question. With the aid of a notion of label uncertainty, we try to address this question in local climate zone (LCZ) classification. Using a deep network as a fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 14 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…We closely follow the code implementation of the authors of [11], which can be found in [25]. We expand the experiments conducted by [19] by adding another deterministic uncertainty quantification technique, DUE. It is here denoted by GP-IP, which stands for a Gaussian Process (GP) output mapping with the inducing points (IP) approximation by [11].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We closely follow the code implementation of the authors of [11], which can be found in [25]. We expand the experiments conducted by [19] by adding another deterministic uncertainty quantification technique, DUE. It is here denoted by GP-IP, which stands for a Gaussian Process (GP) output mapping with the inducing points (IP) approximation by [11].…”
Section: Methodsmentioning
confidence: 99%
“…The OOD detection is carried out by a binary classifier defined by the predictive uncertainties, on which the area under the receiver operator curve (AUROC) and under the precision recall curve (AUPR) are derived. The Dempster-Shafer metric (DSM) and 1 minus the maximum softmax probability (MSP) have already been previously used as uncertainty metric in [19], here the predictive entropy of the softmax prediction (Pred.Ent.) is added specifically for GP-IP approaches.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations